(untitled) (Fiep Bulletin - online, 2014)
Nowadays body-building is one of the ways to prevent chronic degenerative disease and keep a healthy life. Resistance exercises help to make the body composition better and to provide an increase to muscle mass with a good quantity of proteins. The objective of this paper is to verify the body-builder’s macronutrients consumption in a fitness center in Santa Maria-RS. This a transversal exploratory study which uses the sportive nutrition research line with 18 to 25 year-old bodybuilders. A 24h recall was used to verify the macronutrients ingestion and after that DietWin Professional software version 2.0 was used to calculate the number of calories ingested and macronutrients consumed. The FAO/OMS/85 formula and the participant’s current weight were used to determine the energy necessity. Among the evaluated people 55% of the sample was overweight and 45% were eutrophic. In relation to the proteins ingestion 60% of them was ingesting more than the literature recommended and 40% was ingesting the ideal quantity. The body-builders who were not eating the proper quantity of macronutrients can have their performance harmed in the fitness centers and they will not get the waited result: the muscle hypertrophy.